2018
DOI: 10.1590/1678-5150-pvb-5193
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ethylene glycol with sucrose increases survival rate after vitrification of somatic tissue of collared peccaries (Pecari tajacu Linnaeus, 1758)

Abstract: The cryopreservation of somatic tissue in collared peccaries promotes an alternative source of genetic material of this specie. The solid-surface vitrification (SSV) is a great option for tissue conservation; nevertheless, the optimization of SSV requirements is necessary, especially when referred to cryoprotectants that will compose the vitrification solution. Therefore, the aim was to evaluate the effect of the presence of 0.25 M sucrose in addition to different combinations (only or association) and concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…Subconfluent cells were washed with PBS then trypsinized with a trypsin/EDTA solution (0.25%/0.2%) for 7 min and centrifuged at 600×g for 10 min. The supernatant was removed, the cell pellet was resuspended in culture medium, and the cell suspension was transferred to another dish for subculturing (Borges et al, 2018b). The medium was replaced with fresh medium every other day and the cells were monitored daily.…”
Section: Evaluation Of the Somatic Cells In Primary Cultures And Subcmentioning
confidence: 99%
See 2 more Smart Citations
“…Subconfluent cells were washed with PBS then trypsinized with a trypsin/EDTA solution (0.25%/0.2%) for 7 min and centrifuged at 600×g for 10 min. The supernatant was removed, the cell pellet was resuspended in culture medium, and the cell suspension was transferred to another dish for subculturing (Borges et al, 2018b). The medium was replaced with fresh medium every other day and the cells were monitored daily.…”
Section: Evaluation Of the Somatic Cells In Primary Cultures And Subcmentioning
confidence: 99%
“…Briefly, the cells were stained with 0.4% trypan blue in PBS and counted on a hemocytometer. Subsequently, the cells were also analyzed for a metabolic activity using the MTT assay, according to the method described by Borges et al (2018b). A concentration of 5.0 × 10 4 cells/mL from the first, third and tenth passages was grown in 12-well polystyrene plates treated for cell adhesion.…”
Section: Influence Of the Passage Number On The Quality Of Fibroblastmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, 18 we observed by quantitative histology that EG with sucrose resulted in a better conservation of skin tissues derived from collared peccaries; nevertheless, the effect of these cryopreservation solutions on cell recovery after in vitro culture has not yet been observed in the species. Thus, the aim of the current study was to compare the efficiency of various vitrification solutions for recovery of viable cells after in vitro culture of cryopreserved skin tissues derived from collared peccaries.…”
Section: Introductionmentioning
confidence: 82%
“…Embora esta técnica já tenha demonstrado resultados promissores, ainda pode levar a formação de cristais de gelo, e exige o uso de materiais e equipamentos de Research, Society and Development, v. 9, n. 8, e969986686, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i8.6686 valor econômico mais elevado (Borges et al, 2017;Praxedes et al, 2019). Já a vitrificação em superfície sólida, consiste no resfriamento abrupto do tecido sobre uma superfície metálica com a presença de nitrogênio líquido, e posterior armazenamento, sendo esta técnica a mais utilizada nos protocolos de criopreservação de pele (Borges et al, 2018), por ser uma técnica simples e de baixo custo.…”
Section: Introductionunclassified